INNOVATING PV WATER PUMP BUSINESS FOR RENEWABLE ENERGY INDUSTRY IN INDONESIA USING BLUE OCEAN STRATEGY - Eric Harianto; Tiyo Avianto; Riduan Mas'ud; Denpharanto Agung Krisprimandoyo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to investigate and make decisions in determining features, innovation values and business strategies in the renewable energy industry from Sanspower (PT. Java Surya Teknik) which is focused on PV Water Pump products in order to create competitive products for the Indonesian market. Determining the right renewable energy technologies (RET's), as well as a strategy to accelerate commercialization that has different values from competitors, and avoids the red ocean market. This study uses a qualitative methodology using the Blue Ocean Strategy (BOS), testing the data using the triangulation method. This research was started from September 2021 to February 2022 to produce products in the renewable energy industry that are right for the developing country.